Digital Image Watermarking - Al Zaid, Abdullah Saleh (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2009)
This is the Final Project Report as being composed of an extensive summary of activities and results made by the student Abdullah S. A. Alzaid while undertaking the Watermark Project. This project acquaints an algorithm of digital watermarking which is based on Discrete Cosine Transform(DCT) and Discrete Wavelet Transform(DWT). In accord with the characters of human vision, the main objective of the project is to be focused on developing an image watermarking algorithm by taking advantage of both the DCT and DWT transforms and analysis of the algorithm on the basis of invisibility, distortion and robustness to attacks. The simulation results show that this algorithm is invisible and has good robustness for some common image processing operations. By the use of Matlab software, the two structures have been coded and then implemented.

This is the Final Project Report as being composed of an extensive summary of activities and results made by the student Abdullah S. A. Alzaid while undertaking the Watermark Project. This project acquaints an algorithm of digital watermarking which is based on Discrete Cosine Transform(DCT) and Discrete Wavelet Transform(DWT). In accord with the characters of human vision, the main objective of the project is to be focused on developing an image watermarking algorithm by taking advantage of both the DCT and DWT transforms and analysis of the algorithm on the basis of invisibility, distortion and robustness to attacks. The simulation results show that this algorithm is invisible and has good robustness for some common image processing operations. By the use of Matlab software, the two structures have been coded and then implemented.
Digital Image Watermarking
Keywords: watermarking; discrete wavelet transform; discrete cosine transform; watermarking; discrete wavelet transform; discrete cosine transform